The Impact of the Strategic Leadership in Strategic Learning Exploratory Research at Anbar University - Awad, Mahmood J.; Saeed, Muthana M.; Hamid, Mohammed Q. (Journal of Economics and Administrative Sciences, 2021)
This study aims to know the extent of the impact of Strategic Leadership as an independent variable in Strategic Learning as a dependent variable to help the senior leadership in Anbar University to take the right decisions to develop Strategic Learning programs in light of the circumstances of the Covid-19 and the sudden decisions adopted by the university to switch to E-learning and to blend. The survey was conducted by distributing a questionnaire that was adopted as a primary tool in data collection from the study sample represented by the university’s senior leaders, An intentional random sample of (105) was selected from our community of (127), the data were analyzed by (SPSS) Depending on the set of statistical means, including (the weighted arithmetic mean, standard deviation, relative importance, coefficient of variation, coefficient of determination, stability test, ranks correlation coefficient, simple linear regression analysis). The research reached several results, the most important of which is the existence of a strong statistically significant correlation and impact relationship between Strategic Leadership and Strategic Learning in its dimensions at Anbar University, and this means the university leadership was able to find well appropriate solutions to enhance its capabilities in the transformation to strategic learning. Moreover, this study came to complement its ideas brought by previous research on Strategic Leadership and Strategic Learning by proposing a conceptual model that clarifies the interrelationships between the main variables of research and how to adopt them in Iraqi universities in general and Anbar University in particular